New sensing platform of poly(ester-urethane)urea doped with gold nanoparticles for rapid detection of mercury ions in fish tissue. Issue 50 (28th September 2021) - El-Raheem, Hany Abd; Hassan, Rabeay Y. A.; Khaled, Rehab; Farghali, Ahmed; El-Sherbiny, Ibrahim M.
Abstract : A new electrochemical sensor based on poly(ester-urethane) urea doped with gold nanoparticles (PUU/AuNPs) for highly sensitive and selective detection of mercury(ii ) ions in fish tissue. Abstract : A new electrochemical sensor has been fabricated based on the in situ synthesis of poly(ester-urethane) urea (PUU) doped with gold nanoparticles (AuNPs), and the obtained composite materials (PUU/AuNPs) were used as a new sensing platform for highly sensitive and selective detection of mercury(II) ions in fish tissue. PUU was synthesized and fully characterized by XRD, TGA, DSC, and FTIR to analyze the chemical structure, thermal stability, and morphological properties. As a polymeric structure, the PUU consists of urethane and urea groups that possess pronounced binding abilities to Hg 2+ ions. SEM-EDX was carried out to confirm this kind of interaction. Using ferricyanide as the redox probe, PUU alone exhibited weak electrochemical signals due to its low electrical conductivity. Therefore, a new series of nanocomposites of PUU with different nanostructured materials were applied, and their electrochemical performances were evaluated. Among these materials, the PUU/AuNP-modified electrode showed high voltammetric signals towards Hg 2+ . Consequently, the parameters affecting the performance of the assay, such as electrode composition, scan rate, and sensing time, as well as the effect of electrolyte and pH were studied and optimized. The sensor showed a linear range of 5 ng mL −1 to 155 ng mL −1 with the regression coefficient R 2 = 0.986, while the calculated values of the limit of detection (LOD) and limit of quantification (LOQ) were 0.235 ng mL −1 and 0.710 ng mL −1, respectively. In terms of cross reactivity testing, the sensor exhibited a high selectivity against heavy metals which are commonly determined in seafood (Cd 2+, Pb 2+, As 3+, Cr 3+, Mg 2+, and Cu 2+ ). For real applications, total Hg 2+ ions in fish tissue were determined with very high recovery and no prior complicated treatments.